Effects of Ridge Tillage Patterns on Soil Erosion of Sloping Croplands in Black Soil Region of Northeastern China - Mou Tingsen; Shen Haiou; He Yunfeng; Li Chunli; Guo Dan; Liu Dianmin (Shuitu baochi tongbao)
[Objective] The effects of ridge tillage patterns on soil erosion at sloping croplands in the black soil region of Northeastern China were analyzed in order to provide scientific guidance for soil erosion control in this region. [Methods] The simulated rainfall experiments were conducted at the sloping croplands with the 5° and 10° slope gradients. The simulated rainfall intensities were 50 and 100 mm/h. This study took the traditional up-and downslope ridge tillage as the control treatment. The ridge tillage patterns included contour ridge tillage, ridge-furrow intervals tillage, up and down slope ridge + bottom contour ridge tillage, and contour ridge + drainage ditch tillage. [Results] Under the experimental conditions, the contour ridge tillage, ridge-furrow intervals tillage, up and down slope ridge + bottom contour ridge tillage, and contour ridge + drainage ditch tillage effectively regulated runoff and decreased soil erosion, compared with control treatment. However, the regulation effect of different ridge tillage patterns on runoff and erosion decreased with the increase of rainfall intensity and slope gradient. For the 5° sloping cropland, the regulation effect of contour ridge tillage treatment on runoff and erosion was the best. The runoff rates and soil erosion rates were stable below 15.0 mm/h and 0.2 kg/(m2·h). Under the rainfall intensity of the 50 and 100 mm/h, the runoff was reduced 92.3% and 83.9% respectively, and the soil erosion reduced 96.8% and 94.6% respectively, compared with the control treatments. The runoff reduction and soil erosion reduction benefits of ridge-furrow intervals tillage treatment was slightly greater than those of up and down slope ridge + bottom contour ridge tillage treatment at the 5° sloping cropland. For the 10° sloping cropland, the contour ridge tillage treatment showed better soil water storage and soil conservation capacity in the early stage of rainfall events compared with that of the other ridge tillage patterns. However, the ridges were easy to be damaged in the later stage of rainfall events, caused a rapid increase in soil erosion. In contrast, the contour ridge + drainage ditch tillage treatment could store soil and water in the early stage of rainfall events, and better drained away water in the later stage of rainfall events. [Conclusion] As to gentle sloping croplands, the contour ridge tillage and ridge-furrow intervals tillage patterns should be optimized, in the sloping farmland with steep slope, the contour ridge + drainage ditch tillage pattern should be preferred. Therefore, it is suggested to select suitable ridge tillage patterns according to slope gradients and rainfall characteristics.